2020
DOI: 10.1002/fsn3.1966
|View full text |Cite
|
Sign up to set email alerts
|

An antidiabetic nutraceutical combination of red yeast rice (Monascus purpureus), bitter gourd (Momordica charantia), and chromium alleviates dedifferentiation of pancreatic β cells in db/db mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…This finding is supported by the data on wound area reduction, which was greater in the treated groups than in the non-treated group. The underlying mechanism is that MJR enhances the expression of VEGF, increasing the production of hydroxyproline by fibroblasts [4]. High levels of hydroxyproline in the tissue indicate increased collagen content, which is crucial for wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is supported by the data on wound area reduction, which was greater in the treated groups than in the non-treated group. The underlying mechanism is that MJR enhances the expression of VEGF, increasing the production of hydroxyproline by fibroblasts [4]. High levels of hydroxyproline in the tissue indicate increased collagen content, which is crucial for wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, MJR is commonly used as a İD İD İD İD İD İD İD İD coloring agent without altering taste, texture, or odor. In the realm of health, MJR has been found to have cholesterol-lowering and blood sugar-reducing properties [3,4]. Lin's research in 2019 further demonstrated that MJR possesses antioxidant and antibacterial abilities [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is a well-known remedy for treating diabetes mellitus. Within eight weeks of regular consumption can result in decreasing the symptoms of diabetes mellitus like polydipsia, polyuria, and polyphagia (Lu et al, 2020) [89] .…”
Section: Management Of Diabetes Mellitusmentioning
confidence: 99%